Carbon, nitrogen and phosphorus recovery from liquid swine wastes: a review - Montalvo, Silvio; Huiliñir, César; Castillo, Alejandra; Pagés‐Díaz, Jhosané; Guerrero, Lorna (Journal of chemical technology and biotechnology (1986), 2020)
Due to the pollution characteristics of the wastewater generated in piggeries, these waste streams have to be treated before discharging into the environment. These wastes have a high content of organic matter, nitrogen and phosphorus that can be converted or recovered into valuable products. The valuation of swine waste by anaerobic digestion has already been assessed, but no systematic review on the technologies used for recovering nutrients from this waste has been reported to date. Therefore, the present work has the goal of presenting the most studied technologies to different scales of recovery of carbon (i.e. organic matter), nitrogen and phosphorus from swine waste. The main characteristics and parameters of the processes involved in these technologies (mainly air stripping, membrane, enhance biological phosphorus removal and struvite formation) are also highlighted, pointing out its advantages and disadvantages and posing some final feasibility considerations on the subject addressed. Experiments reported in the literature proved that technologies used for nutrient recovery from swine waste are mostly applied to the effluents previously treated by anaerobic digestion as a primary treatment, and greater effort is required for the future implementation of these technologies in large scale. © 2020 Society of Chemical Industry